2020
DOI: 10.3389/fonc.2020.591843
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms in Canine Cancer

Abstract: A plethora of data has highlighted the role of epigenetics in the development of cancer. Initiation and progression of different cancer types are associated with a variety of changes of epigenetic mechanisms, including aberrant DNA methylation, histone modifications, and miRNA expression. At the same time, advances in the available epigenetic tools allow to investigate and reverse these epigenetic changes and form the basis for the development of anticancer drugs in human oncology. Although human and canine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 236 publications
(220 reference statements)
0
10
0
2
Order By: Relevance
“…An addition level of complexity is added through the dynamics of the epigenome, with gene expression regulated by a variety of reversible modifications of DNA or histones, and translation of mRNA influenced by a diverse array of non-coding RNAs [65]. One such epigenetic mark is DNA methylation of cytosine residues in CpG dinucleotides.…”
Section: Epigenetic Alterations In Canine Oral Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…An addition level of complexity is added through the dynamics of the epigenome, with gene expression regulated by a variety of reversible modifications of DNA or histones, and translation of mRNA influenced by a diverse array of non-coding RNAs [65]. One such epigenetic mark is DNA methylation of cytosine residues in CpG dinucleotides.…”
Section: Epigenetic Alterations In Canine Oral Melanomamentioning
confidence: 99%
“…These sites are found in repetitive elements throughout the genome, and clustered in so-called CpG islands (CGI), which are present in the promotor regions of around half of all mammalian genes [66]. While the former are usually methylated, CGIs are frequently unmethylated, and within promoters, methylation can lead to gene silencing, either through a steric interference with transcription machinery, or by recruiting chromatin remodelling factors [65]. A recent canine study has taken an IHC approach with a monoclonal antibody to 5-methylcytosine, revealing predominantly weak staining or negative nuclei in COMs, but staining intensity in normal melanocytes was not determined, and gene-specific methylation was not determined [67].…”
Section: Epigenetic Alterations In Canine Oral Melanomamentioning
confidence: 99%
“…LncRNAs are non-coding transcripts >than 200 bp in length, and different studies demonstrated the influence of these molecules in gene expression at the epigenetic, transcriptional, and post-transcriptional levels. One of the most classical mechanisms through which lncRNAs regulate gene expression involves their association with chromatin modeling complexes and transcription factors, influencing transcriptional repression and activation of gene promoters ( 211 ).…”
Section: Lncrnasmentioning
confidence: 99%
“…Among the multiple epigenetic mechanisms found in canine cancer, DNA methylation and histone modification have been identified on the basis of OSA progression ( 211 ). Le Beguec et al characterized the expression profiles of 10.444 canine lncRNAs in 26 distinct tissue types.…”
Section: Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation